2023
DOI: 10.3390/coatings13010166
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Tunable Tribological Behavior of Shape Memory Biphenyl Epoxy Resin

Abstract: Although polymer-based self-lubricating materials have rapidly developed recently, intelligent lubricating materials with self-adaptable lubrication with external conditions changing are highly demanded, especially for harsh conditions. Herein, a shape memory epoxy resin based on the biphenyl units (BPEP) with tunable tribological behavior was systematically studied. X-ray diffraction (XRD), field emission scanning electron microscope (SEM), laser confocal three-dimensional profiler, and optical microscope wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…However, it was found that PAEK exhibited a specific strain reduction after each shape memory cycle. In other words, dynamic mechanical cycling might cause the benzene ring units in PAEK to reassemble with π–π interaction forces along the stretching direction, resulting in R r values greater than 100% for all PAEK samples as a consequence. , This finding was similar to mechanically responsive self-growing hydrogels which could be made stronger by repeated mechanical stresses that induced physical or chemical structure changes within the polymer . Based on the above investigation, a spring-shaped sample made of P5 was utilized to illustrate the shape memory effect with a greater deformation (Figure g, Video S1).…”
Section: Resultsmentioning
confidence: 82%
“…However, it was found that PAEK exhibited a specific strain reduction after each shape memory cycle. In other words, dynamic mechanical cycling might cause the benzene ring units in PAEK to reassemble with π–π interaction forces along the stretching direction, resulting in R r values greater than 100% for all PAEK samples as a consequence. , This finding was similar to mechanically responsive self-growing hydrogels which could be made stronger by repeated mechanical stresses that induced physical or chemical structure changes within the polymer . Based on the above investigation, a spring-shaped sample made of P5 was utilized to illustrate the shape memory effect with a greater deformation (Figure g, Video S1).…”
Section: Resultsmentioning
confidence: 82%